Illocutionary acts in cars 2 movie - Astawan, I Made Agus; Pratiwi, Desak Putu Eka; Ariyaningsih, Ni Nyoman Deni (Institut Pariwisata dan Bisnis Internasional, 2022)
Language is one of the most important skills people use to interact with other people since people need communication in daily life. Nowadays in helping people to understand language, there are a lot of studies that discuss the language itself. Speech acts are one of the studies that help people to understand language. This study aims to find out types of illocutionary acts as well as their intended meaning. The data were taken from a movie entitled Cars 2. The data were collected by observation method and note taking technique by classifying data based on types of illocutionary acts. The collected data were analysed by descriptive qualitative method by using theory proposed by Yule (1996) and Halliday (1989) to analyse the types and the intended meaning of illocutionary acts uttered by all characters in Cars 2 movie. The finding shows that all types of illocutionary acts found in the movie, they are representative, directive, commissive, expressive, and declaration. The utterances have both explicit and implicit meaning. The implied meaning can be discovered by understanding the context of the situation in that story.